2016
DOI: 10.1111/ics.12341
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in follicles of individuals with female pattern hair loss is associated with perifollicular microinflammation

Abstract: Apoptosis was prominent in hair follicles from the FPHL group, as well as in miniaturized ones. Moreover, it was also correlated with the inflammatory infiltrate, which suggests that inflammation can lead to apoptosis and play a role in the pathogenesis of follicle miniaturization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…The quality of hair shaft and the hair growth may thus be altered , and as the ROS‐detoxifying enzyme tyrosinase‐related protein 2 (TRP2) is not expressed in the hair bulb, the pigmentation process is progressively disturbed, and the hair fibre is greying . The involvement of a micro‐inflammatory cascade in androgenic alopecia has also been pointed out for years , inflammatory cells surround the permanent region of the follicle producing a damaging environment for stem cells . In addition, in vitro studies showed that oxidative stress reduced hair matrix cell proliferation and increased cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…The quality of hair shaft and the hair growth may thus be altered , and as the ROS‐detoxifying enzyme tyrosinase‐related protein 2 (TRP2) is not expressed in the hair bulb, the pigmentation process is progressively disturbed, and the hair fibre is greying . The involvement of a micro‐inflammatory cascade in androgenic alopecia has also been pointed out for years , inflammatory cells surround the permanent region of the follicle producing a damaging environment for stem cells . In addition, in vitro studies showed that oxidative stress reduced hair matrix cell proliferation and increased cell apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Later, Whiting reported the presence of inflammation in 37% of biopsy samples from patients with FPHL compared with 12% of control subjects. Scalp biopsies from 17 women with FPHL and five healthy females were included in the study of Ramos et al . They observed a higher apoptosis index and prominent mononuclear microinflammation among the miniaturized follicles.…”
Section: Pathophysiologymentioning
confidence: 99%
“…DHT, which present 10 times more affinity to androgen receptors compared to testosterone, binds to these receptors in genetically predisposed hair follicles, impairing hair cycle. The landmark decrease of anagen phase occur, anticipating catagen phase in a complex process involving apoptosis as probably microinflammation [10,25]. The involvement of hair follicle microinflammation in AGA is being reported since the 1970s.…”
Section: Pathophysiology Of Agmentioning
confidence: 99%
“…Fibroblasts also respond to pro-inflammatory factors [35] and cellular defenses (neutrophils, T cells, Langerhans cells) are mobilized [36,37]. The inflammation usually persists and may lead to tissue remodeling via collagenases, generating a perifollicular fibrosis [10] and also to apoptosis that has been recently related to follicle miniaturization [25].…”
Section: Pathophysiology Of Agmentioning
confidence: 99%